Evaluation of seasonal variation of groundwater quality by using the correlation matrices method in Koppal Taluk, Karnataka, India - Ramesh Basanagouda; Avinash Pandurang; Maradi Nayaka (Advances in Environmental Technology, 2025)
Groundwater is a vital, renewable resource that provides over 94% of drinking water in most areas and is critical to human health and sustainable development. Groundwater pollution has a significant impact on human health. This study was conducted in Koppal Taluk, Koppal district, Karnataka, India, from December 2022 to November 2023 to assess the physicochemical parameters of groundwater at 25 seasonal sites. Several steel processing industries are located in the study area, and the inhabitants depend on groundwater sources for their daily needs. The study analyzed the parameters of cations and anions as per APHA guidelines. The study started with data standardization using the water quality index (WQI) and subsequent visualization of correlation matrices and mapping of data plots. The method used was ArcGIS 10.8, which visualizes spatial distribution for data quality control, identification of erroneous data, and classification of different data types. WQI values for drinking water ranged from 9.04 to 75.24 and showed three classes that were unsuitable for drinking. The correlation study showed that TDS, TH, Mg2+, Ca2+, and Cl− were more correlated. Most of the limitations were more or less associated with the parameters. Factor analysis suggested the first three principal components (PCs) in this analysis were 96% (Monsoon), 93.50% (Pre-Monsoon), and 87% (Post-Monsoon) of the cumulative variance correspondingly, and TDS was the most representative variable across all seasons.  This study underlined the importance of sustainable development and groundwater protection. The recommendations could help groundwater managers and urban planners to improve and maintain groundwater quality.